Significance of Negative Sentences Structures in the Verses of the Noble Qur’an - Ismail, Abdel Rahim (Islamic Sciences Journal, 2023)
This research sought to reveal the significance of the negative sentences structures in the verses of Tanzih the Noble Qur’an; through using the linguistic and syntactical tools contained in the structures of those sentences. In this research, we concluded that the significance of the structures of the negative sentences in the verses of the honorable Qur’an came in response to the infidels and polytheists who accused the Quran of many charges that have no basis or foundation. These indications varied with the variety of accusations directed at the Quran. Doubt, about alteration, about crookedness, about poetry and fortune-telling, and about the words of devils, and about humor. As for the meaning of the structures of the negative phrasal verbs, the Qur’an is clear about slander, about misery, about demons descending, and about coming up with the like of the Qur’an, and about falsehood, from crookedness, and from whims. What we can conclude from all of this is that the meanings of the negative sentences structures in the verses of the Noble Qur’an came to prove one undoubted fact that the Noble Qur’an is the Book of Allah that He revealed to His Prophet Muhammad (may Allah bless him and grant him peace), and it is free from falsehood and from everything that is not. befitting him; Because it is a download from Hakim Hamid.